Teaching Foreign Oral Speech to Language University's Students on the Basis of Creolized Text - Sergueevna Andrianova, Natalia; Fedorovna Ostroumova, Olga; Anatolyevna Vanchikova, Elena (International Journal of Criminology and Sociology, 2022)
In the context of globalization and international integration, the requirements for knowledge of a foreign language, as an essential component of the professional competence of a modern competitive specialist, have substantially changed. Thus, the purpose of language education in modern conditions is the formation of a secondary linguistic personality, capable of intercultural communication, owning a fluent, clear and logically constructed foreign language speech. This goal leads to the search for creative approaches to professionally oriented teaching of foreign languages, the effectiveness of which is associated with the creation of problematic situations that contribute to unlocking the creative potential of students. Solving problematic problems contributes to the development of critical thinking, creative activity, interest and motivation to learn a foreign language, analytical skills and spontaneous speech of students. In the conditions of information oversaturation in the modern world, creolized texts occupy has a significant place in the communicative space in professional life. It requires a representative of a modern society to have the ability to decode, interpret information. In this study, the authors consider the informational and linguodidactic potential of foreign-language creolized texts, which can be used as the basis for the development of unprepared speech and discussion skills of students in the framework of organizing a creative educational process. Finally, the authors propose a pedagogical algorithm for the formation of communicative skills of students in the context of the development of spontaneous speech based on creolized texts.